AB1223 Ultrasonography examination of elbows is useful when combined with examination of pip and wrist joints. (12th June 2018) - Nakajiama, T.; Shimizu, M.; Hashimoto, M.; Yamamoto, H.; Kawahara, R.; Nakabo, S.; Hiwa, R.; Gon, Y.; Funakoshi, S.; Nakamura, Y.; Sasai, T.; Tomizawa, T.; et al.
Abstract : Background: Because elbows are important joints for the function of upper limbs, the daily activity of the patients with rheumatoid arthritis (RA) may be impaired by synovitis of elbows. Although elbows are included into the 28 essential joints for evaluation of the disease activity of RA, ultrasonography (US) examination of elbows is not routinely performed and there have been a few surveys on the correlation between US scores of elbows and disease activity. Objectives: To reveal whether there is a correlation between US scores of elbows and disease activity in the patients with RA. Methods: We recruited 198 patients with RA form KURAMA cohort, which is the database of the patients with RA treated in the Kyoto University Hospital, and performed US examination of proximal interphalangeal (PIP) joints, metacarpophalangeal (MP) joints, wrist joints and elbow joints. Synovial hypertrophy is scored semiquantitatively on a scale of 0–3. We analysed correlations between the total scores of each component (PIP, MP, wrist and elbow) and clinical parameters. Results: We found weak correlations between DAS28-ESR and the US scores of PIPs, MPs and wrists (rho=0.25, 0.21 and 0.29, respectively) whereas there was little correlation between DAS28-ESR and the US score of elbows (rho=0.16). However, multivariable analysis showed that the US scores of PIPs, wrists and elbows were independently associated with DAS28-ESR (p=0.021, 0.0027 and 0.025, respectively). US scores of elbows showed little or weak correlations with US scores of PIPs, MPs and wrists (rho=0.23, 0.16 and 0.11, respectively). Conclusions: US examination of elbows may be useful to assess the disease activity of patients when combined with US examination of PIPs and wrists although US scores of elbows alone has a weak correlation with DAS28-ESR. US examination of elbows may detect the disease activity which is overlooked by the US examination of joints of hand. Disclosure of Interest: None declared